THE EFFECT OF COVID-19 TO ISLAMIC EDUCATION IN SINGAPORE (THE EXPERIENCE OF MUHAMMADIYAH ISLAMIC COLLEGE) - Saifuddin Amin; Rahmatullah Rahmatullah (Pascasarjana IAIN Metro, 2020)
This paper aims to determine the effect of Covid-19 which is currently hitting the entire world with a very high mortality rate in the world of education, especially the Islamic Education Institution in Singapore, namely the Muhammadiyah Islamic College. With a qualitative method and a literature review approach through the official website of the Singapore government, it was found that MIC took a policy to conduct online learning through zooming and changes to the student evaluation system. With the current excellent acceptance of online learning, it is hoped that an online-based international Islamic university will be built.